العقل و دوره في استنباط األحكام الشرعية )دراسة أصولية( - م.م هاورێ عمر عوال سمايل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Praise is to God and prayers and peace be upon the prophets and messengers and on his family and his companions and after: This research is about (the wisdom role of human in extracting the provisions of the legitimacies) The researcher has talked about the importance of wisdom, Mattresses of wisdom and mind in the Islamic scholars’ point view, particularly Principles of jurisprudence scholars. In fact, conducting a research on wisdom and mind, and also talking about the role and its importance by human, is a response for inviting the holy Quraan, because just the word of (mind) has mentioned (49) times in it and all of them have been used as present tense, and this is an indication for the necessity of generating, using mind and depending by human being. The aim of the research is demonstrating and shining the role of mind by scholars and its effectiveness over extracting the branch jurisprudence and applying of their principles. Also, this research aims to show the scientific level of the Islamic scholars on this field, since having science about mind, wisdom and perceiving wisdom role in legitimate provisions and extracting them have a great effective, in order not to fall mistakes during extracting them form the reliable sources, this makes a learner to understand the secrets of religious law and understanding the legitimate and knowing where the jurisprudence subjects came from, and this will be done through narration of pieces to general and combine them with principles by having evidences.